Analisis Pengalaman Mahasiswa UINSSC Dalam Menggunakan Media Pembelajaran Bahasa Arab Berbasis E-Learning - Maulana, Fahmi; Miftahuddin, Miftahuddin; Rizkya Alfahrezy, Rafly; Irfan Hania (AL MA'ANY, 2025)
Arabic, spoken by over 200 million people, plays a vital role in global communication, information, and scientific exchange. Mastering Arabic facilitates international communication and knowledge sharing. This study highlights four essential language skills: listening, speaking, reading, and writing. Technology, particularly e-learning and Learning Management Systems (LMS), enhances learning effectiveness. However, LMS utilization requires evaluation to ensure efficacy. This research draws on language learning and educational technology theories, employing qualitative methods and case studies to analyze students' experiences. Findings inform the development of more effective LMS applications, technology integration into curricula, and teacher training, ultimately enhancing Arabic language learning quality.